2018
DOI: 10.15244/pjoes/76676
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Nutrient Regime and N:P Ratios on Algal Growth in 182 Korean Agricultural Reservoirs

Abstract: The principal aim of this study was to evaluate how nutrient regime and TN:TP ratios regulate algal chlorophyll in Korean agricultural reservoirs. We developed empirical models of log-transformed CHL-TN:TP ratio based on seasonality. Winter algal chlorophyll was highly influenced by the ratio of TN:TP (R 2 = 0.78, p<0.01) compared to chlorophyll-a in the spring (R 2 = 0.38, p<0.01), summer (R 2 = 0.50, p<0.01), and autumn (R 2 = 0.44, p<0.01), respectively. Regression analysis of log-transformed TN:TP ratios-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Therefore, P was the most limiting primary nutrient to regulate the sestonic Chl-a productivity in the AR. However, in the AR, rather than P, the most critical limiting factor was the N:P ratio, which was strongly supported by several previous studies [2,25,[68][69][70]. Considering the prevalent nutrient and sestonic CHL-a trends, there was no need for immediate and strict plans to mitigate nutrient enrichment to regulate Chl-a and algal blooms in the AR.…”
Section: Empirical Modelling Of Nutrients and Sestonic Chl-asupporting
confidence: 63%
“…Therefore, P was the most limiting primary nutrient to regulate the sestonic Chl-a productivity in the AR. However, in the AR, rather than P, the most critical limiting factor was the N:P ratio, which was strongly supported by several previous studies [2,25,[68][69][70]. Considering the prevalent nutrient and sestonic CHL-a trends, there was no need for immediate and strict plans to mitigate nutrient enrichment to regulate Chl-a and algal blooms in the AR.…”
Section: Empirical Modelling Of Nutrients and Sestonic Chl-asupporting
confidence: 63%
“…The present research observed that summer TP regulates the summer algal growth in Tz (R 2 = 0.24), Lz (R 2 = 0.40), and IT1 (R 2 = 0.18). This scenario had been observed frequently in Asian reservoirs [3,28,29]. In contrast, spring TP influences the summer algal chlorophyll in North American reservoirs [26,27].…”
Section: Discussionmentioning
confidence: 76%
“…Major nutrient inputs occur during the spring season in North American reservoirs, and thus, the spring TP determined the summer algal chlorophyll [26,27]. In contrast, excessive nutrient loading occurs during the summer season in Asian reservoirs; thus the high TP during summer monsoon regulates the summer and autumn algal chlorophyll [3,28,29]. Furthermore, the log-transformed regression empirical models of SD-TP, SD-TN, SD-TSS, and SD-CHL-a have been used to determine the trophic response and water clarity of the systems.…”
Section: Introductionmentioning
confidence: 99%
“…As to phosphorus, the quality water sections of Case II and Case III were 78.41%, 78.36%, and 78.69% from 2016 to 2018, respectively, which indicated that the water quality of the Pearl River was fine for phosphorus. As to the whole basin, the TN/TP ratio of Pearl River was 24.7, exceeding the most suitable molar ratio for plankton growth with an average of 16, which was an over-enrichment of nitrogen relative to phosphorus [10,32,33]. The limitation of low phosphorus would result in excess N being left in the river basin, because of potential limitation both phytoplankton biomass and N utilization [34].…”
Section: Resultsmentioning
confidence: 99%